Alterações antropométricas e metabólicas em escolares de seis a nove anos do município de Vitória - ES - Patricia Casagrande Dias de Almeida (2011)
Background: The prevalence of overweight and dyslipidemia among Brazilian children is rising. Previous studies demonstrated an association between high cholesterol levels in childhood with coronary disease in adult life. Aims: Identify the prevalence of overweight and dyslipidemia in children between six to nine years old enrolled in public schools in Vitória, Espírito Santo State, Brazil. Methods: A transactional study was performed with 620 children from both sexes enrolled in public schools and data related to anthrometry and dyslipidemia was collected. All the children were submitted to a nutritional evaluation and information about body weight, height, abdominal circumference and triceps skinfold thickness was collected. Blood was also collected from some children (511) and analyzed biochemically for total cholesterol, High Density Lipoprotein (HDL-C), Low Density Lipoprotein (LDL-C) e triglicerydes. Statistical Analysis was performed using SPSS version 13 and significance was accepted at the 5% level. Results: When analyzed by the nutritional classification based on BMI/age we found that 2.3% were under weight, 59.7% (370) were with ideal weight, 12.9% (80) were overweight and 25.2% (156) children were obese. The abdominal circumference was defined as normal in 525 (84.7%) and increased in 95 (15.3%) children. The triceps skinfold thickness was defined as normal in 472 (76.1%) and altered in 148 (23.9%). Of the 511 children that allowed the collection of blood 11.92% (61) had trygliceride levels elevated, 62.61% (320) presented high levels of total cholesterol and 40.29% (206) and 26.6% had high levels of LDL-C and low levels of HDL-C, respectively. Conclusions: The results presented here demonstrated that in the population studied high levels of overweight and dyslipidemia was observed, reinforcing the importance of cholesterol dosage in children.